Kekerasan Dalam Rumah Tangga (KDRT) dalam Pernikahan Dini Perspektif Teori Maqashid Syari’ah - Mutakin, Ali; Mustafa, Fitri; Khaeruddin, Khaeruddin; Al Falah, Dzia (STAINI Press, 2023)
The concrete age restriction for marriage has been regulated in Law No. 1 of 1974, which was later revised into Law No. 16 of 2019. The law states that marriage will be permitted if both the bride and groom have reached the minimum age of 19. This restriction certainly has a strong philosophical basis ranging from juridical basis to issues of reproductive health and mental readiness (maturity). This research is a qualitative research with a statutory approach (statute approach) and a conceptual approach. Data is obtained through library research, both primary and secondary data sources. This study concluded that, domestic violence that occurs as a result of marriage carried out by both spouses of the bride and groom where one or both are not old enough as stipulated at 19 years, has a serious impact both on the continuity of the household and others. Maqashid shari'ah whose basis is benefit, either in order to realize the welfare itself or to reject the evil, in order to see the phenomenon of domestic violence that occurs in marriage at an early age. Daf'u al-Dlarar in order to reject domestic violence has at least a significant role to play in resolving such phenomena.